2019
DOI: 10.1109/access.2019.2926327
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Overbooking Policy for Cloud Service Providers: Profit and Service Quality

Abstract: A cloud federation is a current paradigm that enables partnered cloud providers to share idle capacities during low demand periods and to purchase spare resources during demand spikes. In this research, we propose an optimal overbooking policy to maximize federation members' profits and enhance cloud users' experiences. The proposed policy overcomes cloud providers' low utilization and increases their profits. Under the market-oriented cloud federation system, we use the number of idle resources in the cloud f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Thus prevents cloud data center (Hussain anf Sohaib 2019) SLA violation. Yao et al (2019) and Yadav et al (2018) established an effective overbooking model and also accepted the requirements needed for better solutions. Through following the optimum approach, they found that the suggested overbooking technique would raise a federated company's income and reduce the risk of SLA contravention.…”
Section: Introductionmentioning
confidence: 99%
“…Thus prevents cloud data center (Hussain anf Sohaib 2019) SLA violation. Yao et al (2019) and Yadav et al (2018) established an effective overbooking model and also accepted the requirements needed for better solutions. Through following the optimum approach, they found that the suggested overbooking technique would raise a federated company's income and reduce the risk of SLA contravention.…”
Section: Introductionmentioning
confidence: 99%
“…A similar problem is tackled by Roy et al [17] by proposing PRIME, a pricing scheme supporting an optimised and unbiased distribution of profit among different actors in mobile sensor-cloud architectures. Yao et al [3] provide an optimal overbooking policy to maximize providers' profits and enhance cloud users' experiences by decreasing the number of SLA violations. They achieve these goals by establishing a cooperative game model of providers organised in a cloud federation with sharing resources, and making a reasonable profit distribution.…”
Section: A On Pricing Modelsmentioning
confidence: 99%
“…However, only some of the aforementioned authors consider the underlying SLA model in their proposals [3], [20]. As far as we know, these works do not allow describing billing discounts as opposed to our proposal, even though they are commonly specified in customer agreements by cloud providers.…”
Section: A On Pricing Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overbooking: "Booking" refers to a presale manner (rather than spot trading), where "overbooking" presents the presale of a volatile commodity or service in excess of actual supply, which has been shown to provide substantial utilization and profit advantage under "no shows" (some consumers will cancel the trading of requested service) [8], which, however, has been neglected in most previous mentioned works (namely, these works mainly consider equal-booking where the amount of resources for sale equals to the actual supply). The widespread adoption of overbooking techniques focus on many fields such as airlines and hotels [9], [10], spectrum reservation [11], [12], storage market [29], network slicing [30]- [32], cloud computing [7], [33]- [36], and fog computing [37]. Specifically, Liu et al in [11] proposed an opportunistic link overbooking scheme for an edge gateway to improve its link efficiency, and developed an integrated analytical framework for determining the suitable link overbooking factor.…”
Section: Messous Et Al Investigated the Computation Offloading Proble...mentioning
confidence: 99%